2018
DOI: 10.3390/jfb9010019
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Metallic Glasses as Structural Materials for Cardiovascular Stent Applications

Abstract: Functional and mechanical properties of novel biomaterials must be carefully evaluated to guarantee long-term biocompatibility and structural integrity of implantable medical devices. Owing to the combination of metallic bonding and amorphous structure, metallic glasses (MGs) exhibit extraordinary properties superior to conventional crystalline metallic alloys, placing them at the frontier of biomaterials research. MGs have potential to improve corrosion resistance, biocompatibility, strength, and longevity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 249 publications
(409 reference statements)
0
44
0
1
Order By: Relevance
“…Recently, metallic glasses (MGs) have received considerable attention for biomedical device applications owing to their structural and functional properties, many of them superior to those of conventional metallic alloys (e.g., SS 316L). MGs display high strength, hardness, resilience, corrosion resistance, and biocompatibility . MGs are obtained by rapid quenching from the melts of alloys, which prohibits formation of a crystalline solid as in conventional alloys, and leads to an amorphous (glassy) solid structure .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, metallic glasses (MGs) have received considerable attention for biomedical device applications owing to their structural and functional properties, many of them superior to those of conventional metallic alloys (e.g., SS 316L). MGs display high strength, hardness, resilience, corrosion resistance, and biocompatibility . MGs are obtained by rapid quenching from the melts of alloys, which prohibits formation of a crystalline solid as in conventional alloys, and leads to an amorphous (glassy) solid structure .…”
Section: Introductionmentioning
confidence: 99%
“…A drawback of MGs is their lack of tensile ductility due to severe localization of plastic deformation in narrow bands (so called shear bands) upon their yield. It has been recently shown that by considering certain design criteria, the superior resilience of MGs could be exploited for self‐expandable stent applications which do not need plastic deformation during the stent crimping and deployment process . Nevertheless, the lack of ductility in MGs prohibits them to be used in balloon expandable stent applications where plastic (permanent) deformation is crucial for their deployment process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations